TRANSVERSAL COMPETENCIES FOR DIGITAL READINESS AND DEVELOPMENT OF HUMAN CAPITAL IN ENGINEERING EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The research is carried out within the framework of Rezekne Academy of Technology, Latvia in cooperation with West Ukrainian National University, Ukraine LV – UA project “Gender aspects of digital readiness and development of human capital in regions” Nr.LV-UA/ 2018/3.Nowadays, educational institutions have to adapt to the new situation, make changes that would promote the transformation of the study process, promote the development of digital readiness and human capital.The aim of the research is to study the need for transversal competencies, innovation, entrepreneurship and development of digital readiness and human capital in engineering studies. The monographic and descriptive method has been applied for studying scientific literature and modeling method for a professional development plan.